Etude quantitative des activités nucléotidases des cellules végétales : - Rôle dans la régulation de la charge énergétique. - Présence et fonctionnement dans le tonoplaste - Nhiri, Mohamed (Université Paris-Sud XI, Centre D'Orsay, 1991)
This manuscript brings to contributions in the field of plant celles nucleotidases. Using elaborated HPLC techniques, the osmotic stress, occuring when protoplasts are prepared, was described in terms of energectic charge of adenylic nucleotides. The HPLC was suitable to give the nucleotides balance and kinetics of their evolution in various conditions. From these experiments it was suggested that the integity of the plasmalemma and the regulation of the energic charge could be determininig in regeneration studies. Since osmotic regulation involves vacuoles, the interaction betwenn adenylic nucleotids and tonoplast xas carefully examined using HPLC. Besides the ATPase activity, a new phosphotransferase activity was characterized on this membrane which converted ADP into ATP and AMP. This illustrated the interest of HPLC in nucleotides enzymology where the usual methods could not detect interconversion. Il was also demonstrated that pyrophosphate could be an energy source by reversing the ATPase hydrolyzed by tonoplast and their ability to generate a proton gradient was compared to ATP. GTP ant ITP were significantly hydrolyzed without important contribution to the proton gradient. All these result illustrate the complexity of the nucleotide metabolism particularly in the vacuolar compartment and open new perspectives in plant protoplasts culture and regeneration.
Keywords: Etude quantitative; Activité nucléotidase; Cellule végétale; Charge énergétique; Présence; Fonctionnement; Tonoplaste